Gene Drives at Tipping Points Precautionary Technology Assessment and Governance of New Approaches to Genetically Modify Animal and Plant Populations - von Gleich, Arnim; Schröder, Winfried (Springer Nature, 2020)
This open access book reports on a pilot project aiming at collecting information on the socio-ecological risks that could arise in the event of an uncontrolled spread of genetically engineered organisms into the environment. The researchers will, for instance, be taking a closer look at genetically engineered oilseed rape, genetically engineered olive flies as well as plants and animals with so-called gene drives. The book mainly adresses researchers.